Effects of Yoga in Patients with Chronic Heart Failure: A Meta-Analysis - Mansueto Gomes-Neto (Arquivos Brasileiros de Cardiologia, 2014)
The use of yoga as an effective cardiac rehabilitation in patients with chronic heart failure (CHF) remains controversial. We performed a meta-analysis to examine the effects of yoga on exercise capacity and health-related quality of life (HRQOL) in patients with CHF. Methods: We searched MEDLINE, Cochrane Central Register of Controlled Trials, Excerpta Medica database, LILACS, Physiotherapy Evidence Database, The Scientific Electronic Library Online, and Cumulative Index to Nursing and Allied Health (from the earliest date available to December 2013) for randomized controlled trials (RCTs) examining the effects of yoga versus exercise and/or of yoga versus control on exercise capacity (peakVO2) and quality-of-life (HRQOL) in CHF. Two reviewers selected studies independently. Weighted mean differences (WMDs) and 95% confidence intervals (CIs) were calculated, and heterogeneity was assessed using the I2 test. Two studies met the selection criteria (total: 30 yoga and 29 control patients). The results suggested that yoga compared with control had a positive impact on peak VO2 and HRQOL. Peak VO2, WMD (3.87 95% CI: 1.95 to 5.80), and global HRQOL standardized mean differences (-12.46 95% CI: -22.49 to -2.43) improved in the yoga group compared to the control group. Yoga enhances peak VO2 and HRQOL in patients with CHF and could be considered for inclusion in cardiac rehabilitation programs. Larger RCTs are required to further investigate the effects of yoga in patients with CHF.